2010
DOI: 10.1121/1.3462232
|View full text |Cite
|
Sign up to set email alerts
|

Automatic identification of individual killer whales

Abstract: Following the successful use of HMM and GMM models for classification of a set of 75 calls of northern resident killer whales into call types [Brown, J. C., and Smaragdis, P., J. Acoust. Soc. Am. 125, 221–224 (2009)], the use of these same methods has been explored for the identification of vocalizations from the same call type N2 of four individual killer whales. With an average of 20 vocalizations from each of the individuals the pairwise comparisons have an extremely high success rate of 80 to 100% and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Third, MFCCs show high accuracy, stability, and repeatability (Cheng et al 2010). And finally, MFCCs are now also increasingly applied to caller recognition of animals such as elephants (Clemins et al 2005), passerine birds (Trawicki et al 2005;Fox 2008;Cheng et al 2010), toothed whales (Brown et al 2010), and blue monkeys (Mielke and Zuberbühler 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Third, MFCCs show high accuracy, stability, and repeatability (Cheng et al 2010). And finally, MFCCs are now also increasingly applied to caller recognition of animals such as elephants (Clemins et al 2005), passerine birds (Trawicki et al 2005;Fox 2008;Cheng et al 2010), toothed whales (Brown et al 2010), and blue monkeys (Mielke and Zuberbühler 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gaussian Mixture Models (GMMs) and Support Vector Machine (SVM) algorithms have been used to construct cetacean species detectors to discriminate between signals produced by Blainville’s beaked whales ( Mesoplodon densirostris ), short-finned pilot whales ( Globicephala macrorhynchus ), and Risso’s dolphins ( Grampus griseus ) 20 ; and similar computational techniques have been implemented in an effort to estimate sperm whale size distributions 21 . It has been demonstrated that a radial basis function network could effectively distinguish between six individual sperm whales 22 ; and similarly, Hidden Markov Models (HMMs) and GMMs have performed the automatic identification of individual killer whales ( Orcinus orca ) 23 . In addition, ANNs have been constructed to classify the bioacoustic signals of killer whales based on call type, individual whale identity, and community dialect 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…calls, vocalization, echolocation trains and clicks) in a specific type of noise [33]. A plethora of tools from pattern to voice recognition has been developed to build signal detectors relative to a single species or group of affiliate species [35,[40][41][42][43]. Automatic detection of biological signals at higher organization levels (communities) has been rarely pursued [12,44] owing to difficulties in dealing with other sources of sounds (anthropogenic or geophysical noise).…”
Section: (A) Bioacoustic and Ecoacoustic Indexesmentioning
confidence: 99%